Lets make k equal to Kate's age and j equal to Joey's age. If in 5 years Kate will be twice as old as Joe, you can write the equation k+5=2(j+5) and then simplify it to make it easier to work with. k+5=2(j+5) k+5=2j+10 k+5-2j=10 k-2j=5 since we know that right know Kate is 11 years older than Joey, you can write the equation k+j=11. Since you know have two equations with with the same variable, you can make a system of equations as fallows: k-2j=5 k+j=11
Since you need to figure out how old Joey is, you need to somehow get k to cancel out. The easiest thing to do for this problem is to is multiply the top equation by -1 to get: -k+2j=-5 (you have to add the bottom equation to the top equation) k+j=11 (-k+k=0, 2j+j=3j, and -5+11=6) Since k got canceled out, you are left with the equation 3j=6 which means j=2. Therefore, Joey's current age is 2.